2001
DOI: 10.1038/35089104
|View full text |Cite
|
Sign up to set email alerts
|

A giant chlorophyll–protein complex induced by iron deficiency in cyanobacteria

Abstract: Cyanobacteria are abundant throughout most of the world's water bodies and contribute significantly to global primary productivity through oxygenic photosynthesis. This reaction is catalysed by two membrane-bound protein complexes, photosystem I (PSI) and photosystem II (PSII), which both contain chlorophyll-binding subunits functioning as an internal antenna. In addition, phycobilisomes act as peripheral antenna systems, but no additional light-harvesting systems have been found under normal growth conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
246
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 333 publications
(268 citation statements)
references
References 23 publications
(1 reference statement)
11
246
0
Order By: Relevance
“…Furthermore, a group of genes encoding polypeptides related to the early light-inducible proteins (ELIP) and LHCs of higher plants, the one-helix high-light-inducible proteins [HLIP, for reviews see Green and Durnford (1996); Montané and Kloppstech (2000)] has been found in cyanobacteria (Funk and Vermaas 1999). The results presented here, however, constitute the first evidence on protein level for membrane intrinsic light harvesting proteins in cyanobacteria besides the most recently found IsiA ring (Boekema et al 2001).…”
Section: Biochemical Propertiesmentioning
confidence: 58%
See 2 more Smart Citations
“…Furthermore, a group of genes encoding polypeptides related to the early light-inducible proteins (ELIP) and LHCs of higher plants, the one-helix high-light-inducible proteins [HLIP, for reviews see Green and Durnford (1996); Montané and Kloppstech (2000)] has been found in cyanobacteria (Funk and Vermaas 1999). The results presented here, however, constitute the first evidence on protein level for membrane intrinsic light harvesting proteins in cyanobacteria besides the most recently found IsiA ring (Boekema et al 2001).…”
Section: Biochemical Propertiesmentioning
confidence: 58%
“…This would imply the necessity for one or more additional chlorophyll bearing polypeptides on which the superfluous Chl molecules could be organised. One attractive hypothesis would be that Gloeobacter contains additional membraneintegral light-harvesting proteins resembling the LHC proteins found in chloroplasts or the recently found CP43 (Riethman and Sherman 1988;Park et al 1999) or IsiA (Boekema et al 2001;Bibby et al 2001) in cyanobacteria. Such a hypothesis would support the assumption that Gloeobacter is the predecessor of chloroplasts.…”
Section: Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…It allows imaging of a large range of objects, from biological systems, e.g. cells7 or proteins,8, 9 to materials,10 aggregating of surfactants11, 12 and other self‐organising molecules into structures such as gels13 and vesicles 14. It is widely applied in both biology and organic and polymer chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the up-regulation of "homologous recombination" might result in an increase of DNA mismatch repair and recombination [39]. Detailed analysis of genes with the same change trends (up-or downregulated) in both PMM and PMT under iron depletion condition suggested the mechanism that cyanobacteria employ to iron deficiency could be: firstly transporters were activated to obtain more iron from the environment [25], and photosynthesis and chlorophyll metabolism was inhibited due to the limited supply of iron [40][41][42], and then oxidative stress was enhanced and may cause RNA degradation, protein translation inhibition and other cellular metabolic changes. All these further resulted in inhibition of DNA replication and cell cycle block, and eventually growth cease.…”
Section: Construction Of Cyanobacteria Metal Response Networkmentioning
confidence: 99%